Profil Kelengkapan Informasi oleh Apoteker tentang Cara Penggunaan Sediaan Handihaler® yang Mengandung Tiotropium Bromida Di Apotek Wilayah Surabaya Timur - Amelia Lorensia; Doddy de Queljoe; Yessica Christina Wijaya Tandjung (Jurnal Sains dan Kesehatan, 2019)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic disease that can be controlled with medication. Handihaler® may be an option in the control of COPD, but the use of techniques Handihaler® is lacking in patients can cause treatment to be not optimal, therefore, the role of pharmacists to explain how to use Handihaler®. This study aims to investigate the characteristics of how to use information given Handihaler® pharmacists in pharmacies in East Surabaya. This research is non-experimental research with cross sectional method, and using observation techniques in the form of a checklist. Sampling by non-random sampling method by using purposive. The data will be processed with descriptive statistical analysis. The research sample as many as 22 pharmacies. The results showed that the steps 1, 2, 3, and 4 can be explained properly, whereas no pharmacist to explain step 16. Therefore, community pharmacists need to increase knowledge to support the pharmacist's role in providing information on how to use inhalers to improve the effectiveness COPD therapy.